Dampak Terorisme terhadap Perdamaian dan Keamanan Internasional: Tinjauan Terhadap Penanganan Kasus Terorisme oleh Mahkamah Pidana Internasional - Marthin Susanto; Nuradilla Maharani Rosyaputri; Ikhsan Sugiri; Adinda Putri Maharani; Herli Antoni (Badan Penerbit STIEPARI Press, 2023)
International terrorism is a crime that must fulfill an international element, involving more than one country as perpetrator, victim and funding. The main aim of this crime is to attack world peace and security. To deal with international terrorism crimes, regulations are needed at both the national and international levels. The International Criminal Court (ICC) has an important role in handling terrorism crimes. The aim of this research is to evaluate the effectiveness and challenges faced by the ICC in handling criminal acts of terrorism. To overcome these challenges, stronger international cooperation is needed in exchanging information and extradition of terrorist perpetrators. Apart from that, it is also necessary to increase the capacity and resources of the ICC to increase its effectiveness in handling terrorism cases.